DCRMRP: distributed cooperative relay-based multihop routing protocol for WiMedia networks. (2017) - Umadevi, K.S.; Thangavelu, Arunkumar
WiMedia plays a major role in the domain of personal area networks owing to its ability to support high data rate. It is used for constructing home networks, establishing virtual multimedia connectivity for video or audio sharing and so on. Maximising the utilisation of the available resources in an efficient manner is one of the objectives in wireless networks. In order to provide better resource utilisation, parameters such as resource allocation, provisioning and monitoring need to be considered. In extremely occupied situations, mobility, interference and link quality may also be addressed. Poor link quality results in slow and unreliable network connection. Therefore, resource provisioning with good signal strength is a challenging task. By considering the mobility and link quality factors along with relaying concept, a simple distributed cooperative relay-based routing protocol is designed to reduce the resource starvation and enhance the utilisation for WiMedia. Unlike conventional routing algorithms, the proposed approach minimises the delay, which in turn maximises the throughput by choosing a better link quality.